Transformation in Biology Learning during the Covid-19 Pandemic: From Offline to Online - Kintan Limiansi; Anggi Tias Pratama; Rizqa Devi Anazifa (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2020)
This article aims to describe the implementation of online biology learning in senior high schools (SMA/MA) in the Special Region of Yogyakarta during the pandemic. This study employed a quantitative method and involved 25 SMA/MA biology teachers in the Special Region of Yogyakarta. The data were collected through a survey by distributing questionnaires to the teachers. The results reveal that all SMA/MA biology teachers in Yogyakarta have transformed offline learning into online learning. They conduct blended online learning by combining virtual synchronous activities and asynchronous activities by utilizing online media. The virtual synchronous activities (44%) dominate the learning process, and thus, conducive communication between teachers and students is created. Whatsapp is the most dominant media utilized in the virtual synchronous activities (38%) and asynchronous activities (41%) even though this application is not designed for learning purposes. This study is expected to provide SMA/MA biology teachers’ objective description of their condition in implementing online learning. Consequently, the description can become an evaluation for educational stakeholders and a consideration to conduct related research.